Etika Komunikasi Mahasiswa Kepada Dosen Di Jurusan Dharma Duta Institut Agama Hindu Negeri Gde Pudja Mataram - Puja Alingga Sugyana; I Wayan Ardhi Wirawan; Sayu Kadek Jelantik (PT. Gauri Narendra Patraka, 2023)
The study was done to study the implementation of student ethics communication ethics to lecturer at Dharma Duta Department of Institute Agama Hindu Negeri Gde Pudja Mataram. The research methods used are qualitative using data collection techniques of participle, structured interviews, and documentation. Data analysis techniques through three ways means are data reduction, data presentation, and deduction. The study used communicative action theoriesof Jurgen Habermas to dissect each formulation of problems. The result of this study is that a student's form of communication ethics to professors occurs directly and indirectly through text messages or telephone calls. Factors that influence a lack of a student's ethics of communication to a lecturer include (1) a lack of understanding of a communication ethic, (2) a closeness to a lecturer, (3) a lack of knowledge of language ethics, (4) a student's character lacking in a communication ethic, (5) a social environment. The strategy in building a quality communication ethic between teachers and students is that the first students need to realize the importance of honoring lecturer as teachers in a Hindu sense. Second, students need to know, understand, and apply rules about ordinances to contact the lecturer who has been prescribed by the campus. Third, a student's openness with a lecturer on something that can trigger discomfort while communicating.